Implementasi Metode Flat Pada Sistem Informasi Akuntansi Pinjaman Sebagai Perhitungan Angsuran Berbasis Web - Ahmad Ashifuddin Aqham (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The need for technology is greatly needed by various groups, both in the world of education, in companies and government agencies as a solution to these problems. One of them is implementing an accounting information system for inputting, processing or reporting accounting in the company. This application can produce data processing quickly and accurately. This certainly saves a lot of time and also reduces errors that occur when work is done manually. Likewise with cooperatives, cooperatives also need to use an accounting information system to make their work faster and more accurate. The activities carried out at Primkopti